Acute fatigue predicts sickness absence in the workplace: A 1‐year retrospective cohort study in paediatric nurses. (5th July 2017) - Sagherian, Knar; Unick, George J.; Zhu, Shijun; Derickson, Debra; Hinds, Pamela S.; Geiger‐Brown, Jeanne
Abstract: Aims: To examine the relationship between fatigue and sickness absence in nurses from a paediatric hospital over 12 months of follow‐up. A secondary aim was to identify other work and personal factors that predict sickness absence. Background: Sickness absence is often related to worker‐fatigue, yet few studies have explored this relationship in nurses despite documented high fatigue levels. Design: The study used retrospective cohort design. Methods: Baseline data on 40 nurses from an intervention study were linked to absence data using the hospital's attendance records (2012–2013). A total of 6, 057 work shifts were studied of which 5.2% were absence episodes. Fatigue was measured by the Occupational Fatigue Exhaustion Recovery scale. The questionnaire included instruments assessing sleep disturbances, workload and personal characteristics. Generalized linear mixed models were used to test the associations between fatigue, work, personal factors and sickness absence, while accounting for non‐independency of repeated measures. Results: With 1SD increase in acute fatigue scores, nurses were 1.29 times more likely to be absent from work. Factors such as intershift recovery, perceived workload, obstructive sleep apnoea and marital status also predicted sickness absence, that is, with 1SD increase in workload scores, nurses were 1.23 times more likely to be absent from work. Nurses with obstructive sleep apnoea had two times higher odds of sickness absence. Conclusion: Sickness absence is related to acute fatigue in paediatric nurses and to workload. Nursing leaders can monitor these factors to reduce sickness absence and screen for sleep apnoea and assist nurses in receiving the appropriate treatments.